Pengaruh Partisipasi terhadap Kepuasan Pemakai dalam Pengembangan Sistem Informasi dengan Kompleksitas Tugas, Kompleksitas Sistem, dan Pengaruh Pemakai sebagai Moderating Variable - Nurika Restuningdiah; Nur Indriantoro (The Indonesian Journal of Accounting Research, 2013)
The relationship between user participation and user satisfaction in the system development process still becomes the interesting problem, because there has not been consistent empirical result. In seeking to explain such equivocal results, the effect of three contingency factors- task complexity, system complexity,  and user influence— on the relationship between user participation and user satisfaction were investigated. As suggested in the literature, this research tests hypotheses that these spesific contingency factors should aid in identifying situations where user participation would have a strong relationship with satisfaction.Analysis of 102 midle managers from different organization, who become the respondents, indicated that user participation has direct relationship with user satisfaction. The contingency factors were found to play key roles on this relationship.. Task complexity and system complexity proved to be quasi moderator, so that in the  high level of task and system complexity, the relationship between user participation and user satisfaction was significantly stronger than in project where task and system complexity was low. User influence was shown to be quasi moderator on the relationship between user participation and user satisfaction.The implications of this study is relevant to system developers and to academicians seeking to explain how and why user participation is needed. The results help explain the relationship between user participation and user satisfaction by suggesting the nature of the relationship under different sets of conditions.